2005
DOI: 10.1186/cc3538
|View full text |Cite
|
Sign up to set email alerts
|

Drotrecogin alfa (activated) in patients with severe sepsis presenting with purpura fulminans, meningitis, or meningococcal disease: a retrospective analysis of patients enrolled in recent clinical studies

Abstract: IntroductionWe report data from adult and pediatric patients with severe sepsis from studies evaluating drotrecogin alfa (activated) (DrotAA) and presenting with purpura fulminans (PF), meningitis (MEN), or meningococcal disease (MD) (PF/MEN/MD). Such conditions may be associated with an increased bleeding risk but occur in a relatively small proportion of patients presenting with severe sepsis; pooling data across clinical trials provides an opportunity for improving the characterization of outcomes.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Or, practically speaking, after a lumbar puncture is performed upon admission (for which prior reversal of anticoagulant therapy is necessary), is it advisable to immediately resume anticoagulant therapy? Previous studies on the effect of anticoagulant therapies in bacterial meningitis showed a higher rate of hemorrhagic complications and mortality [14], [15]. In a retrospective analysis of several open-label, placebo controlled and compassionate-use trials of activated protein C (APC), intracranial hemorrhage was seen in 6% of patients treated with APC compared to 3% of patients receiving placebo or no APC.…”
Section: Discussionmentioning
confidence: 99%
“…Or, practically speaking, after a lumbar puncture is performed upon admission (for which prior reversal of anticoagulant therapy is necessary), is it advisable to immediately resume anticoagulant therapy? Previous studies on the effect of anticoagulant therapies in bacterial meningitis showed a higher rate of hemorrhagic complications and mortality [14], [15]. In a retrospective analysis of several open-label, placebo controlled and compassionate-use trials of activated protein C (APC), intracranial hemorrhage was seen in 6% of patients treated with APC compared to 3% of patients receiving placebo or no APC.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Patients with an infection of the head or neck, however, were not included in these trials, and it is unknown whether this recommendation should apply to these patients. Limited data suggest that anticoagulant therapy in patients with meningitis is associated with a higher rate of intracerebral hemorrhagic complications 15 and increased mortality. 16 With the exception of case reports, 17,18 there are no data on the use of heparin in patients with CVT and a concurrent infection.…”
mentioning
confidence: 99%
“…Other studies have explored the use of activated PC in patients with PF. Vincent and colleagues published a post-hoc analysis of recent studies using activated PC in adult and pediatric patients with severe sepsis, presenting with PF, meningitis or meningococcal disease [ 5 ]. The authors identified 119 pediatric patients suitable for the analysis, 87 of them with PF.…”
Section: Discussionmentioning
confidence: 99%